2011
DOI: 10.1177/1470320311412811
|View full text |Cite
|
Sign up to set email alerts
|

The long-term antiproteinuric effect of eplerenone, a selective aldosterone blocker, in patients with non-diabetic chronic kidney disease

Abstract: The long-term administration of low-dose eplerenone was effective and safe for the treatment of non-diabetic CKD patients who showed persistent proteinuria in spite of therapy with RAS inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
4
7
0
3
Order By: Relevance
“…Second, after administration of eplerenone, the amount of proteinuria reduced. This effect was consistent with a previous study which showed antiproteinuric effect of the addition of low-dose eplerenone (25–50 mg/day) to renin-angiotensin system blockers in nondiabetic chronic kidney disease patients [14]. Recent studies suggested that aldosterone exerts deleterious effects in the vascular system and kidney independently of angiotensin II [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Second, after administration of eplerenone, the amount of proteinuria reduced. This effect was consistent with a previous study which showed antiproteinuric effect of the addition of low-dose eplerenone (25–50 mg/day) to renin-angiotensin system blockers in nondiabetic chronic kidney disease patients [14]. Recent studies suggested that aldosterone exerts deleterious effects in the vascular system and kidney independently of angiotensin II [15].…”
Section: Discussionsupporting
confidence: 92%
“…In this patient, there was no remarkable fall in blood pressure after administration of low-dose eplerenone (fig. 2), suggesting effects of eplerenone might be mediated by BP-independent mechanisms [14, 15, 16, 17]. A prospective cohort study will be required to clarify the characteristics of regimen-sensitive patients.…”
Section: Discussionmentioning
confidence: 99%
“…в своей работе (2011) [52] оце-нивали эффективность и безопасность использова-ния эплеренона у пациентов с ХБП без сахарного диа-бета. У пациентов, получающих АМКР в течение 12 мес, экскреция белка с мочой снизилась на 38% в сравне-нии с контрольной группой.…”
Section: эплеренон и протеинурияunclassified
“…Факт снижения протеин-урии у пациентов, которым назначался эплеренон, интересен еще и тем, что препарат назначался в отно-сительно низкой дозировке (25-50 мг/сут). Примеча-тельно, что случаев гиперкалиемии в данном иссле-довании не отмечалось, что указывает на высокий уровень безопасности эпреленона [52]. Эти данные со-гласуются с результатами предыдущих исследований, которые указывают на низкую частоту гиперкалиемий у пациентов с ХБП [53][54][55][56][57][58][59].…”
Section: эплеренон и протеинурияunclassified
“…Eplerenone (Ep) has also been shown to have anti-proteinuric effects, but a high prevalence of non-responders were found in the same study. 12 Presently, it is not known what causes the differences between responders and non-responders, but Yoneda et al have shown that subjects who developed higher aldosterone concentration (aldosterone breakthrough) 13 are more likely to develop proteinuria. Moranne et al found that initial plasma potassium and aldosterone concentrations, as well as higher decreases in sodium intake, systolic BP (SBP), and estimated GFR (eGFR) from baseline to 1 year were factors that influence plasma aldosterone level.…”
Section: Introductionmentioning
confidence: 99%